2022
DOI: 10.1002/chem.202201115
|View full text |Cite
|
Sign up to set email alerts
|

Chemically Modified Poly(A) Analogs Targeting PABP: Structure Activity Relationship and Translation Inhibitory Properties

Abstract: Poly(A)-binding protein (PABP) is an essential element of cellular translational machinery. Recent studies have revealed that poly(A) tail modifications can modulate mRNA stability and translational potential, and that oligoadenylate-derived PABP ligands can act as effective translational inhibitors with potential applications in pain management.Although extensive research has focused on protein-RNA and protein-protein interactions involving PABPs, further studies are required to examine the ligand specificity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 54 publications
0
0
0
Order By: Relevance
“…Interestingly, those differ from the sequences investigated by Perzanowska et al (2022). In particular, the pair of sequences having highest affinity in the study, was not found in our list.…”
Section: Designcontrasting
confidence: 62%
See 1 more Smart Citation
“…Interestingly, those differ from the sequences investigated by Perzanowska et al (2022). In particular, the pair of sequences having highest affinity in the study, was not found in our list.…”
Section: Designcontrasting
confidence: 62%
“…To illustrate the capacity of MFEdock to address design, we considered a design study recently published by Perzanowska et al (2022), where an oligonucleotide targeting a poly(A)-binding protein (PDBID: 1CVJ) was designed. Since this study included modified nucleotides, we considered an extended list of nucleotides: two without modification (A,G), and 5 with modifications: adenosine and guanosine with a phosphorothioate (AP , GP ), protonated adenosine (A ψ ), N6-methyladenosine (m 6 A), N6-methyladenosine including phosphorothioate (m 6 AP ), O-methyladenosine (Am) and Omethyladenosine including phosphorothioate (AmP ).…”
Section: Designmentioning
confidence: 99%